EKSISTENSI KELUARGA DALAM PEMENUHAN HAK ATAS PENDIDIKAN ANAK DI MASA PANDEMI COVID-19 - Bambang Hadi Cahyono (Institut Agama Islam Negeri Ponorogo, 2021)
Abstract: This article aims to discuss the existence of families in fulfilling children’s education during the Covid-19 pandemic. The existence of the Covid-19 pandemic has quite large implications in all aspects of life, both from economic, health, social, political and educational aspects. The government issued a policy regarding provisions in regulating education from school to home, in fact it caused various problems that were felt by both parents, especially for children. The existence of families, namely parents, both fathers and mothers, who initially paid less attention and education to their children because children have studied at school, now must provide more optimal care and education to maintain and increase children’s learning motivation. Not only that, parents as teachers must also provide maximum education in order to create motivation in children to be able to carry out learning activities so that existing goals can be achieved even during the Covid-19 pandemic.Keywords: Family existence, children’s education, Covid-19 PandemicAbstrak: Artikel ini bertujuan untuk mendiskusikan tentang eksistensi keluarga dalam pemenuhan pendidikan anak dimasa pandemi covid-19. Adanya pandemi covid-19 cukup menimbulkan implikasi yang besar dalam segala aspek kehidupan, baik dari aspek ekonomi, kesehatan, sosial, politik serta pada aspek pendidikan. Pemerintah mengeluarkan kebijakan mengenai ketentuan dalam mengatur pendidikan dari sekolah ke rumah ternyata menimbulkan berbagai masalah yang dirasakan baik orang tua terlebih bagi anak. Eksistensi keluarga yakni orang tua baik ayah maupun ibu yang semula kurang memberikan perhatian dan edukasi terhadap anak karena anak telah belajar disekolah, kini harus lebih memberikan pengasuhan sekaligus edukasi yang optimal untuk menjaga dan meningkatkan motivasi belajar anak. Tidak hanya itu, orang tua sebagai guru juga harus memberikan edukasi yang maksimal agar terwujud motivasi dalam diri anak untuk dapat melakukan aktivitas belajar agar tujuan yang ada dapat tercapai meskipun pada masa pandemi covid-19.Kata kunci: Eksistensi keluarga, pendidikan anak, Pandemi Covid-19